Expressões da subjetividade ensaística nos curtas-metragens Carlos Nader (1998) e cinema contemporâneo (2019) - Menezes, Lucas dos Santos (2023)
The present work seeks to establish relationships between the short films Carlos Nader (1998) by the director Carlos Nader and Cinema Contemporâneo (2019) by Felipe André Silva, based on the understanding of both audiovisual works as essay films, a category that is built in the modern period of cinema, but which gains greater prominence especially in contemporary times. It is based on the theoretical-conceptual scope, on the studies of Corrigan (2015) and Teixeira (2015) to deal with the expression of subjectivity present in the films worked from the enunciation of a subject who presents himself in the first person, but who dissolves in the gesture of placing oneself in relation with the public sphere, thus producing the figuration of a thought that goes beyond the territory of what would be a strictly private experience. The approximation between the two works more consistently manifests the expression of essay subjectivity, in its movements of insertion and disconnection from itself.